Post-operative capsular opacification - Raj, SM; Vasavada, AR; Johar, SR Kaid; Vasavada, VA; Vasavada, VA (Nepalese Journal of Ophthalmology, 2010)
Post-operative capsular opacification (PCO) is a multifactorial physiological consequence of cataract surgery. Opacification involving the central posterior capsule has a significant impact on high and low contrast acuity and low contrast sensitivity. The assessment of PCO on cadaver eyes, experimental studies and culture models and in clinical studies has provided an understanding of its pathogenesis. The proliferation, migration and abnormal differentiation of residual lens epithelial cells and fibers in the capsular bag have been implicated in the pathogenesis of PCO. The incidence and severity of PCO correlates to the use of surgical techniques, intraocular lens (IOL) optic edge designs and IOL materials. This article summarizes the clinical studies with recommendations for retarding the development of central PCO. It discusses experiments with pharmacological agents broadly categorized as anti-inflammatory, immuno-modulating, antiproliferative, antiadhering and antitransdifferentiating agents for the prevention of PCO. These studies will remain critical for future endeavors undertaken for the eradication of PCO. Key words: posterior capsular opacification; capsular opacification; cataract; crystalline lens; phacoemulsification DOI: 10.3126/nepjoph.v1i1.3673 Nep J Oph 2009;1(1):43-59